2022
DOI: 10.1111/auar.12372
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Tax Avoidance and Corporate Social Responsibility Disclosure Readability: Evidence from China

Abstract: Paying taxes to support the societies in which they operate is both a legal and ethical responsibility of business. Nevertheless, some companies work to avoid taxes, which could cause society to question the legitimacy of the organisation. Many companies provide reports on their corporate social responsibility (CSR) activities; more transparent CSR reports may help to restore the legitimacy loss associated with tax avoidance. We investigate the relationship between tax avoidance and CSR report readability amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 133 publications
(278 reference statements)
0
11
0
5
Order By: Relevance
“…Previous studies have concluded that Chinese SOEs have a different tax strategy compared with non-SOE firms since they are also the collectors and beneficiaries of the tax payments (e.g., Bradshaw et al 2019;Tang 2020;He et al 2021;Xu et al 2022). Specifically, Bradshaw et al (2019) examine publicly traded firms in China and find significantly lower tax avoidance by SOEs relative to non-SOEs.…”
Section: Channel Tests 2: the Types Of Institutional Ownershipmentioning
confidence: 99%
“…Previous studies have concluded that Chinese SOEs have a different tax strategy compared with non-SOE firms since they are also the collectors and beneficiaries of the tax payments (e.g., Bradshaw et al 2019;Tang 2020;He et al 2021;Xu et al 2022). Specifically, Bradshaw et al (2019) examine publicly traded firms in China and find significantly lower tax avoidance by SOEs relative to non-SOEs.…”
Section: Channel Tests 2: the Types Of Institutional Ownershipmentioning
confidence: 99%
“…The inclusion of (sustainable) corporate governance mechanisms will better reflect stakeholder interests and increase legitimacy toward society. Studies on other firm characteristics as (non) financial resources found that CSR performance (Li et al , 2022; Nazari et al , 2017; Wang et al , 2018), total assets and leverage (Raimo et al , 2022), and tax avoidance (Xu et al , 2022) positively impact readability of sustainability reports. As tax avoidance contrasts CSR, there may be a decoupling process as using sustainability reporting for self-impression management and symbolic actions.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
“…First, we build upon the existing literature (Du & Yu, 2021; Nazari et al, 2017; K. Wang et al, 2018; Xu et al, 2022) by empirically testing the impact of institutional investors on CSR readability and considering the moderating effect of ESG performance. Second, we explore the impact of different institutional investors on CSR report readability, considering the heterogeneity of these investors (see, e.g., Z.…”
Section: Introductionmentioning
confidence: 99%